Crop Residue as Beef Cattle Feed Resources for the Development of Integrated Crop-Livestock Systems - Syamsu, Jasmal Ahmari; Yamin, Abdul Alim (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
In Indonesia, livestock development is crucial in improving human resources and determining the future of a nation. The quality of human resources is influenced by the level of food consumption, especially animal-sourced protein consumption obtained from livestock. The consumption of animal protein is 16.67 grams per capita per day and contributes 25.8% to total protein consumption. Consumption of animal-based food such as meat is 4.46 grams, and eggs and milk are 3.43 grams per capita per day. The contribution of animal protein consumption is 0.76 grams per capita per day. Beef demand has rapidly grown over the past few years in Indonesia, but it is not matched by a significant increase in domestic beef production. One of the problems is the availability and continuity of the feed. Therefore, crop residue is a potential feed resource that can be used as an alternative feed. The integrated crop-livestock system can be a solution to overcome feed availability for beef cattle. For this reason, crop residue identification and mapping should be conducted in each region (province, regions/cities) to generate the database for development planning policy involved in the development area of a crop-livestock system based on the specific location for the appropriate crop. Keywords: beef cattle, crop residue, integrated farming, rice straw, corn